Influência da música religiosa na saúde física e mental: uma análise sobre o estresse. - Cardoso, Marlise (2012)
Religious music in our daily lives has left us more relaxed and ready for our daily activities and leisure. When by chance, let us connect with that kind of music we realize that the flow of everyday life will lose its radiance and enchantment. When we hear music or sing toward the spiritual aspects, we feel that the environment is illuminated in such a way that there are changes in our faces leaving us less stressed, balancing emotions, relieving the stresses of daily tasks, leaving our "being" entranced harmonious peace around us. Thus objectives of this study were to investigate whether the religious music influences physical and mental health through an analysis of stress, and how religious music can influence stress; also examine the correlation between the act of listening to religious music and its effects on stress. This is an exploratory descriptive study with quantitative approach, performed in an Evangelical Church, located in the district of Bessa, the city of João Pessoa, Paraíba. It's a church connected to Protestantism, which seeks the evangelization of the members of the same, in search of the encounter and spiritual comfort. Protagonists of this study were 50 people. Data collection occurred from October/2011 to March/2012 and make it viable three instruments were used type questionnaire, namely: Questionnaire Socio-Demographic and characterization, the indices of stress and personality pattern type A, Inventory of Stress Symptoms for adults LIPP (ISSL). Regarding the analysis of data, quantitative grouped and tabulated in Excel and analyzed using statistical and presented in the form of tables with absolute numbers and percentages, graphs and tables statements. It was found that adding the young adult and adult collaborators in the study totaled 43, representing 86% of study collaborators with age in both sexes ranging from 25 to over 59 years. It was also observed that 94% of the employees of the research, stated that the entrance into religious music took place voluntarily. Most adolescents participate in activities and religious rituals in religious institutions, or 54%. Some players said that the meaning of their lives is found in involvement with religious music. Thus, one can see how important and relevant involvement with religious music, religious issues are present in every action of each of the interviewees. Today many young people are making their participation in religious music groups, your leisure, and thus having a fun sound, and this routine feeds on your physical and mental well being. The dedication of the time to do practice meditation, prayer, relaxation or the like, these days, since the daily rush can not take much time to activities that often give much pleasure, and thus minimizes the harmful effects stress in the lives of the interviewees. The study met the proposed objectives and will certainly contribute for assistance that group, since it will allow the stakeholders to devise strategies that contribute to improving the quality of life and spiritual welfare of those. It will also contribute to further research in this area.